Determination of the Accumulation of the Heavy Metal Content of the Sediment of River Danube by Plants - Kovács-Bokor, Éva; Kiss, Endre (International Journal of Engineering and Management Sciences, 2018)
In these days, the surface waters and their floodplains and oxbow lakes are operating as ecological corridors, although their touristic role is not negligible. The monitoring and saving of these wetlands need for sustain these areas for the future generations. The environmental parameters of floodplains and oxbow lakes is revealed with the analyses of the quality of the water and sediment. The main sampling place of our research is a sediment dump was created by excavation from the Open Beach of Dunaújváros in 2009. In 2010 the whole sediment dump was planted with trees, and many kinds of weeds were also grown here. The main aim of this research is to analyse the heavy metal content of the sediment dump in Dunaújváros. Furthermore, the heavy metal content of the parella (Rumex obtusifolius L.), perennial rye-grass (Lolium perenne) and riparian sedges (Carex riparia) which are growing on the sediment dump were also analysed. The distribution and the accumulation of the heavy metals inside this plant can be also determined with these measurements.